2015
DOI: 10.5901/mjss.2015.v6n5p96
|View full text |Cite
|
Sign up to set email alerts
|

Stake Holders’ Perceptions in a Campus Recruitment Process

Abstract: Campus recruitment is a job selection process in which the Industry visits the educational institutions to hire students. In India, the majority of the fresh graduates hiring happens through campus recruitments.The study captures perceptions of the HR1 managers and students on some of the components in a campus recruitment process. It tried to correlate the perceptions of the students and HR managers on Dream company offer, slot sharing, choice of a company, preparation for the recruitment process and the timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Good rankings also positively affect the race for students, who are an important resource in the highly competitive education sector (Tilak, 2016). Another aspect when it comes to recruiting new students is a high placement rate with companies, which is important for students choosing an appropriate college (Raya et al, 2015).…”
Section: Attractiveness and Ilsmentioning
confidence: 99%
“…Good rankings also positively affect the race for students, who are an important resource in the highly competitive education sector (Tilak, 2016). Another aspect when it comes to recruiting new students is a high placement rate with companies, which is important for students choosing an appropriate college (Raya et al, 2015).…”
Section: Attractiveness and Ilsmentioning
confidence: 99%
“…A report of India’s National Association of Software and Service Companies (NASSCOM, 2011) found that only 25 per cent of students graduating in India possessed the requisite employability skills – this compels business corporations to target the most talented students despite the availability of a large student base (Dhingra, 2017). Raya et al (2015) found that human resources managers placed greater importance on the improvement of the soft skills of graduates so that they could communicate their subject knowledge. Kandiko and Mawer (2013) observed that students were not satisfied with their institutional offerings and expected value for money in the form of improved employability and an ability to meet labor market expectations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baird and Parayitam (2019) identified the top six skills that employers wanted as: interpersonal skills, problem-solving skills, listening skills, communication skills, professionalism and personal motivation. These priorities are also important for HEIs: the more students who find placements, the more the institution’s brand worth is raised, making it more attractive for student enrolment and increasing the competition among employers to recruit talented graduates (Raya et al, 2015).…”
mentioning
confidence: 99%
“…Therefore, campus placement basically refers to visit/presence of recruiting organizations in the college where students study and who provide students an opportunity to earn a job placement in their organization by conducting interviews and evaluations in facilitation with college. This arrangement have created win-win situation all round for Students, Employers and Educational Institutions ' [1]. Campus Placement interviews today are administered either through written tests or essays, face to face, panel or direct personal interviews, topic speaking and Group Discussions.…”
Section: Introductionmentioning
confidence: 99%